Systematic study of flow vector fluctuations in √ˢɴɴ =5.02 TeV Pb-Pb collisions - Acharya, S.; Adamovã, D.; Agarwal, A.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akindinov, A.; et al. (American Physical Society, 2024)
Measurements of the Pᴛ-dependent flow vector fluctuations in Pb–Pb collisions at √ˢɴɴ = 5.02 TeV using azimuthal correlations with the ALICE experiment at the Large Hadron Collider are presented. A four-particle correlation approach [ALICE Collaboration, Phys. Rev. C 107, L051901 (2023)] is used to quantify the effects of flow angle and magnitude fluctuations separately. This paper extends previous studies to additional centrality intervals and provides measurements of the Pᴛ-dependent flow vector fluctuations at √ˢɴɴ = 5.02 TeV with two-particle correlations. Significant Pᴛ-dependent fluctuations of the V ⃗₂ flow vector in Pb–Pb collisions are found across different centrality ranges, with the largest fluctuations of up to ∼15% being present in the 5% most central collisions. In parallel, no evidence of significant Pᴛ-dependent fluctuations of V ⃗₃ or V ⃗₄ is found. Additionally, evidence of flow angle and magnitude fluctuations is observed with more than 5σ significance in central collisions. These observations in Pb–Pb collisions indicate where the classical picture of hydrodynamic modeling with a common symmetry plane breaks down. This has implications for hard probes at high Pᴛ, which might be biased by Pᴛ-dependent flow angle fluctuations of at least 23% in central collisions. Given the presented results, existing theoretical models should be reexamined to improve our understanding of initial conditions, quark–gluon plasma properties, and the dynamic evolution of the created system.
Keywords: Physics; Algorithm; Combinatorics; Mathematics; https://purl.org/pe-repo/ocde/ford#1.01.01